Developing a Local Wisdom-Based Learning Model through Sugarcane Bagasse Cracker Innovation to Enhance Elementary Students’ Social Competence and Economic Independence - Sigit Nurhendi; Mubarok Fatahillah; Ulfain; Abdul Aziz; Rochanda Wiradinata; Wartoyo (LJPI UI Bunga Bangsa Cirebon, 2026)
Objective: This study aims to develop a local wisdom-based learning model through sugarcane bagasse cracker innovation to enhance elementary students’ social competence and economic independence. Novelty: This research integrates local wisdom with product-based learning using sugarcane bagasse as an innovative medium to promote sustainability, entrepreneurship, and social skills in primary education. Methods: This study employed a Research and Development (R&D) design adapted from the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were elementary school students and teachers. Data were collected through observations, questionnaires, expert validation sheets, and performance assessments, and analyzed using both qualitative and quantitative techniques. Results: The findings indicate that the developed learning model is valid, practical, and effective. Expert validation results show high feasibility, while implementation demonstrates significant improvements in students’ social competence—such as collaboration, communication, and responsibility—as well as their economic independence reflected in entrepreneurial awareness and basic production skills. Conclusion: The developed model is effective in integrating local wisdom and life skills, contributing to meaningful and contextual learning in elementary education.